A Christmas Story - Dania, Deji (Literamed Publications Nigeria Limited, 2009)
The Virgin Mary received Angel Gabriel's message of the birth of Jesus,the Christ and Saviour of the world.Much later,he is born in the manger,in the city of Bethlehem. Shepherds from the fields,and wise men from the east come to see and worship the new born king.
Keywords: Christianity; Bible Stories; Religion